Development of a novel cell traction force transducer based on cholesteryl ester liquid crystals: characterisation, quantification and evaluation of a cholesteryl ester liquid crystal based single cell force transducer system - Chin, Fhong Soon (2011)
In biomechano-transducing, cellular generated tension can be measured by soft substrates based on polymers but these techniques are limited either by spatial resolution or ability to detect localised cell traction forces (CTF) due to their non-linear viscous behaviour under shear rates. A newly developed cell traction force transducer system based on cholesteryl ester lyotropic liquid crystals (LCTFT) was developed to sense localised traction forces of human keratinocyte cell lines (HaCaTs), in which the length of the deformation line induced represents the intensity of the CTF exerted. The physical properties of the cholesteryl ester based lyotropic liquid crystals (LLC) were characterised by using polarising microscopy, rheology, atomic force microscopy (AFM) based nano-indentation, spherical indentation, and micro-tensile tests. The interactions of LLC with cells were studied by using cell viability studies, cytochemical treatments, widefield surface plasmon resonance (WSPR) microscopy and various immuno-staining techniques. The results show that LLC is thermally stable (0 - 50 OC) PTTA PERPUSTAKAAN TUN KU TUN AM IN AH and linearly viscoelastic below 10 % shear strain at shear rates of < 1 s-l. AFM nano and spherical indentations show a good agreement on the Young's modulus of both determined at "110 kPa which is close to the elastic modulus of the epidermis. The Poisson's ratio of LLC was determined at "0.58 by using micro tensile tests. The biophysical interaction studies indicated that LLC is biocompatible and allowed cell attachment. Cell relaxation technique by cytochalasin-B treatment suggested that the attachment and contraction of cells on LLC was due to the contractile activity of actin cytoskeletons that are mediated by focal adhesions. The staining experiments showed that cells consistently expressed the same suites of integrins (a2, a3, a5 and pl) and ECM proteins (collagen type IV, laminin and fibronectin) on both glass and LLC coated substrates. Interfacial interaction of cells with LLC observed via the staining of actin and vinculin, and WSPR imaging suggest the association of marginal actin filaments and focal adhesions in attaching HaCaT cells to the LLC. Linear static analysis applied in the Finite Element model of focal adhesion-LC confirmed the compressive force patterns induced by cells. By applying cell relaxation techniques and Hooke's theorem, the force-deformation relationships of the LLC were derived and used for direct quantification of CTF in culture. The sensitivity of the LCTFT was implied by a wide range of CTF (10 - 140 nN) measured at high resolutions ("2 pm) Nonetheless, a custom-built cell traction force measurement and mapping software (CTFM) was developed to map CTF of single cells. Reliability of the LCTFT was evaluated by using a known pharmacological active cytokine, TGF-p1, in inducing contraction of human keratinocytes. This study inferred internal consistency and repeatability of the LCTFT in sensing contraction responses of HaCaT cells in a concentration dependent manner of TGF-PI. The overall LCTFT and CTFM software had shown good potential for use in the study of contraction and migration of keratinocytes